2014
DOI: 10.1016/j.watres.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound, low-temperature thermal and alkali pre-treatments on waste activated sludge rheology, hygienization and methane potential

Abstract: Waste activated sludge is slower to biodegrade under anaerobic conditions than is primary sludge due to the glycan strands present in microbial cell walls. The use of pre-treatments may help to disrupt cell membranes and improve waste activated sludge biodegradability. In the present study, the effect of ultrasound, low-temperature thermal and alkali pre-treatments on the rheology, hygienization and biodegradability of waste activated sludge was evaluated. The optimum condition of each pre-treatment was select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(40 citation statements)
references
References 52 publications
(73 reference statements)
3
27
1
Order By: Relevance
“…Although ultrasonication was expected to disrupt the flocs and cellular membranes, the LB-EPS content did not increase as much as it did during the alkali or thermal treatments. This is consistent with the results obtained in a previous work, where the ultrasound treatment was effective enough to dissipate sludge flocs but not for killing bacteria and spores or for inactivating bacteriophages [26]. The TB-EPS fraction was slightly decreased after the ultrasound and alkali treatments and noticeably decreased after the thermal treatment.…”
Section: Amino Acid Concentration (G/g Ts)supporting
confidence: 92%
“…Although ultrasonication was expected to disrupt the flocs and cellular membranes, the LB-EPS content did not increase as much as it did during the alkali or thermal treatments. This is consistent with the results obtained in a previous work, where the ultrasound treatment was effective enough to dissipate sludge flocs but not for killing bacteria and spores or for inactivating bacteriophages [26]. The TB-EPS fraction was slightly decreased after the ultrasound and alkali treatments and noticeably decreased after the thermal treatment.…”
Section: Amino Acid Concentration (G/g Ts)supporting
confidence: 92%
“…With regard to this, the major concern is waste activated sludge (WAS) since common sludge minimization methods such as anaerobic digestion and dewatering process are far from being optimized for WAS [1,2]. The complex structure of WAS flocs which primarily consists of extra polymeric substances (EPS), makes the process of breaking down the cell walls and releasing the bound water in the anaerobic digester and dewatering process so hard [3].…”
Section: Introductionmentioning
confidence: 99%
“…inhibitory impact of some of chemical pretreatments on microorganisms in anaerobic digestion). Ruiz-Hernando et al (2014) [2] compared ultrasound, low-temperature thermal and alkali pre-treatment processes and reported ultrasound as the most expensive method. Appels et al (2010) [4] reported high temperature thermal-pretreatment (>180°C) produced toxic or inhibitory products which resulted in reducing the biodegradability of sludge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different pretreatment methods have been studied to improve the anaerobic degradability of sewage sludge including thermal hydrolysis, ozone oxidation, alkaline hydrolysis, and ultrasound [6][7][8][9]. Among these, ultrasonication is a well-known method to break-up microbial cells and to extract intracellular material [10].…”
Section: Introductionmentioning
confidence: 99%